Effects of FeNi3 Nanoparticles and Coal Slag on Mechanical and Durability Properties of Concrete against Acidic Environments - Hossein Rezayt Khargerdi; Seyed Mojtaba Movahedifar; Alireza Motavalizadehkakhky; Amin Honarbakhsh; Rahele Zhiani (Advances in Civil Engineering)
In recent years, natural pozzolans have been proposed as a way to improve the mechanical and biocompatible properties of concrete. This study investigated the effects of different amounts of nanoparticles, coal slag pozzolan, and their combination on the mechanical properties and durability of concrete. For each mixed design, nine cubic samples of 10 × 10 × 10 cm and 30 × 15 cm were made and then cured in water for 28 days before being tested for compressive and tensile strength. According to the results, pozzolan at about 5% of cement weight increased the compressive strength of concrete compared to samples without pozzolan. Nanoparticles of FeNi3 greatly enhanced the compressive and tensile strength of concrete in most samples containing nanoparticles. The compressive and tensile strength of 28-day concrete increased by 27% and 18%, respectively. Pozzolan (10%) and 2% of FeNi3 (CP10F2) in concrete also reduced the water absorption of the samples, which can improve the durability parameters of concrete. In concrete exposed to sulfuric acid, sample CP0F2 (2% of FeNi3 nanoparticles) had a positive effect on compressive strength, and samples containing 2% of FeNi3 nanoparticles had higher compressive strength than those with pozzolan replacing cement. The simultaneous use of coal slag and FeNi3 nanoparticles has increased the mechanical properties and durability of concrete in addition to reducing cement consumption.